International conception of multicultural education (Pedagogy of Higher and Secondary Education, 2013)
Pogrebnyak V. А.  International conception of multicultural education.The pedagogical analysis of international conception of multicultural education is carried out. The prospects of multicultural approach embodiment into the native educational system in the context of integration of Ukraine to the world and European community are exposed.
Keywords: multicultural education; multicultural educational environment; international conception of multicultural education; multicultural competence